Information (Dis)order: where do we Turn – Towards Confrontation or Dialogue? - Balčytienė, Auksė (Žurnalistikos tyrimai, 2024)
This paper proposes the idea of “information integrity,” conceptualized as a multidimensional strategy to bring together groups entangled in polarizing discourses and vested interests. The paper employs a threefold analytical approach, examining the “macro-mezzo-micro” levels to explore the social interests at each level. Furthermore, it argues that adopting a normative ideal of seeking social solidarity and informed citizenship necessitates changes from within the communications system itself. Such a task requires clarifying the gaps in the current system of knowledge production and proposing actions led by the media corporations themselves and by socially responsible professionals who want to play an active role in addressing society’s grand challenges.
Keywords: information disorder; disinformation; polarization; socially responsible media; information integrity; societal resilience